Convective dynamics in mantle of tidally-locked exoplanets - Daisuke Noto; Takehiro Miyagoshi; Tomomi Terada; Takatoshi Yanagisawa; Yuji Tasaka (Nature Communications)
Abstract Tidal locking imposes distinctive thermal forcing on super-Earth exoplanets in habitable zones, i.e., permanent stellar flux forces extraordinary day-night temperature contrast. However, it may be premature to conclude that life is absent in such supposedly harsh environments—flaming hot on dayside and freezing cold on nightside—when accounting for unobservable features, such as internal convective dynamics and their consequential impact on the surface environment. We establish a simplistic but canonical framework scalable for modeling the convective dynamics in the mantle of tidally-locked exoplanets. The laboratory experiments unveiled an everlasting system-scale circulation that localizes mass and heat transport inside the mantle for a wide range of parameters. We identified the governing parameters that characterize the mass and heat transport of the system and demonstrated their significance. The permanently anchored internal convective structures will be integrated as extraordinary tectonic and deep core activities that differ substantially from those on Earth. In particular, a gradually varying heat flux distribution from the substellar to antistellar points hints at the presence of liquid water in the mid- to high-latitudes due to their moderate geothermal heating, which can potentially host and nurture life on such faraway worlds.